REFRACTIVE LASER SURGERY: WHAT’S NEW? - Lobo Ribeiro, Antonio B (2018)
The correction or improvement of common vision problems (such as, myopia, hypermetropia and astigmatism) through refractive laser surgery, as a permanent alternative to eyeglasses or contact lenses, has been growing in demand over recent years. The most common refractive laser surgery is the laser in-situ keratomileusis (LASIK) and its recent technological variants with improvements. Nevertheless, the generality (if not all), these ophthalmic laser procedures are based in the same physical principle: the reshaping of the cornea and thus altering its optical properties in order to improve vision. Here, the authors attempt to describe in general terms, a very promising, refractive laser procedure much less invasive that doesn’t alter the shape or thickness of the cornea and probably overcomes some limitations of usual LASIK procedure.